Serum cytokines and anxiety in adolescent depression patients: Gender effect. Issue 1 (30th September 2015) - Pallavi, Pooja; Sagar, Rajesh; Mehta, Manju; Sharma, Subhadra; Subramanium, Arulselvi; Shamshi, Farah; Sengupta, Utpal; Pandey, Ravindra M.; Mukhopadhyay, Asok K.
Abstract: The present study compares the serum cytokine levels between adolescent depression patients and healthy controls and assesses correlation between depression, anxiety scores and serum levels of eight cytokines. Study also checked the variation in serum levels with medication status (medication free/naïve vs. patients on medication). Following clinical and psychometric assessment of 77 adolescent (aged 13−18 years) depression patients (49 males and 28 females; 56 medication free/naïve) and 54 healthy controls (25 males, 29 females), eight cytokines (IL-1β, IL-2, IL-6, IL-10, TNF-α, IFN-γ, TGF-β1 and IL-17A denoted IL-17 throughout) were measured in serum using ELISA. Depressed adolescents had significantly high levels of IL-2 ( p <0.001) and IL-6 ( p =0.03) as compared to controls. The female population skewed the result of one cytokine (IL-6) in patients. Anxiety scores showed positive correlation (only in female patients) with IL-1β, IL-10 and negative correlation with TGF-β1 and IL-17. The gender effect in relationship between anxiety and cytokines was not straightforward. On comparing study groups on the medication/naïve status, IL-2 and TGF-β1 showed significant difference between the groups ( p <0.001, p =0.007 higher in medicated). Depression in adolescents was associated with elevation of proinflammatory serum cytokines with a gender bias for females. Anxiety scores correlated negatively with TGF-β1 and IL-17. Highlights: Case-Control study of 77 depressed adolescents and 54 healthy volunteers. Eight serum cytokines were measured on the study subjects. Elevated serum IL-2 and IL-6 found in patients compared to controls. Serum IL-1β, IL-10, TGF-β1 and IL-17 correlated with anxiety in patients There is a gender bias in findings.